AN ANALYSIS OF ENGLISH CLASSROOM INTERACTION USING FLANDER INTERACTION ANALYSIS CATEGORIES SYSTEM (FIACS) TECHNIQUE - Laeli Sinarti; Iwan Jazadi; Supriadin; Furqanul Hakim (STKIP Paracendekia NW Sumbawa, 2023)
The purpose of this study was to determine the percentage of teacher and student talk time and to determine the characteristics of teachers and students during class interaction at SMAN 1 Lunyuk in the 2017/2018 academic year. The design of this study is a mixed method, using descriptive qualitative and quantitative descriptive methods or a combination of qualitative and quantitative methods. Qualitative methods were used to analyze data using Flander's theory and quantitative methods were used to determine the percentage of teacher and student talk time using the Flanders formula. Subjects numbered 30 students with 12 girls and 18 boys. The research data were analyzed by observation, recording, transcripts, coding, then the data were analyzed using the Flanders formula. The results show that asking is the most frequently used by speaking teachers. The percentage of teacher talk is (56.0%) and the percentage of student talk is (33.9%), while the percentage is silent/confused is 10.1%. This shows that teacher talk is the most dominant class interaction during observation. From these results, the researcher concluded that the interaction during the teaching and learning process involved teachers and students and the percentage of teacher and student talk time in class interaction was almost balanced and students were quite active in English class interactions.